Current prospects of successful therapeutic procedures in advanced stage melanoma – the short review - Jarosz, Piotr Michał; Wiśniewska, Patrycja; Czyżewska, Izabela (Journal of Education, Health and Sport, 2020)
Introduction and purpose: Melanoma is the most aggressive form of skin cancer with a rapid course of disease in advanced stage according to the melanoma staging system of the American Joint Committee on Cancer (AJCC). Its morbidity has increased from 20th century. Intermittent sun exposure, age and skin phenotype are included into main risk factors of melanoma. The gold standard in diagnostic and therapeutic procedures is the naevus excisional biopsy associated with histopathology examination. The knowledge about immune system and melanoma biology have enabled therapeutic advantages, such as immunotherapy and molecular target therapy. Objective: To review currently available data on PubMed about current prospects of successful therapeutic procedures in advanced stage melanoma. A brief description of the state of knowledge: A systemic complementary therapy and non-specific immunotherapy are used for treatment advanced-stage-melanoma patients. Current knowledge has enabled an implementation of molecular target therapy in advanced stage melanoma. Evidence based science has yielded promising results and it has included these therapies to the clinical practice, especially molecular target therapy and immunotherapy as well. BRAF inhibitors including vemurafenib, dabrafenib and MEK inhibitors including trametinib are considered to medicaments, that have molecular mechanism of action. Nivolumab, pembrolizumab, ipilimumab are examples of monoclonal antibodies, which are used as an immunotherapy. Conclusions: Excisional biopsy associated with histopathology have been an essential element in therapeutic and diagnostic procedures. Current achievements of medicine sciences have shed light on biology and pathogenesis highlighting the role of immunotherapy and molecular target treatment as well.